Investigating the mechanical and physical properties of wood plastic composites (WPC) - Kamel, Mokhtar Aly Nour El-Din (AUC Knowledge Fountain, 2010)
Wood and plastic wastes have been a major environmental concern not only in Egypt but also worldwide. Plastic wastes are classified as recyclable plastic such as bottles and non-recyclable plastic such as plastic bags especially contaminated bags (rejected plastic). Plastic waste is a non biodegradable material calling for an appropriate method of disposal; however, the current approach adopted in Egypt relies mainly on throwing away in dumpsites. Therefore, it is a costless raw material which needs to be invested. In this thesis, the wood waste and the rejected plastic were recycled to produce new useful product; Wood Plastic Composite (WPC), having characteristics similar or close to commercial wood. An innovative, clean, cheap, and effective yet simple technology with different procedures was introduced in this thesis to demonstrate the suitability of wood plastic composites' techniques for developing countries. Testing was done for some important mechanical properties; flexural strength and modulus, and physical properties; water absorption and thickness swelling, which has proven an acceptable final product and promising results; especially regarding the physical test. The design and analysis of experimental work was built on using design of experiments. Special type of experimental designs; design with mixtures, was adopted because it deals with dependent factors; mixture ingredients. Talc was added to the mixture as a mineral additive. The impact of factors (wood waste, plastic waste, and talc) on the physical and mechanical properties of the WPC (flexural strength and modulus, water absorption and thickness swelling) was investigated based on full analysis of variance (ANOVA). It showed that the plastic waste was the most negative affecting factor; this was contributed to the variability in batches produced in addition to the impurities content. Talc resulted in increasing the flexural strength and modulus. Wood with size of up to 0.5mm has proven to affect the flexural modulus response negatively; when increased. A mathematical model and a response surface representing the factors and their responses; that could be used for future forecasting of the properties without performing physical experiments, were obtained for flexural strength and modulus after conducting several trials till reaching the final experimental design within the navigation space. All these trials were based on an algorithm that was introduced to reach the best feasible model and response surface. A completed residual analysis of the model was done in every trial of the algorithm; where every point within the design was analyzed, till reaching the final model. The best possible mix that enhances the flexural strength to the maximum possible was obtained when the talc was close to 30%, plastic waste 50% and wood waste (of particle size up to 1.18mm) and wood waste (particle up to 0.5mm) of average percentages of 10%. For the flexural modulus, best mix values were obtained when talc is close to 35%, plastic waste 40%, and wood waste (particle up to 1.18mm) about 15% and wood waste (particle up to 0.5mm) 10%. A comparison study; using hypothesis testing, between 7 types of commercial wood (plywood, pinewood, beech wood, maple wood, Fiberboard, Medium Density Fiber wood (MDF), and compressed wood) and WPC was conducted to validate the application of the WPC. It showed that the WPC had the lowest water absorption and thickness swelling percentages compared to others (maximum of 1.7%, average of 0.4% and standard deviation of 0.28%); in addition, it showed that WPC flexural strength performs like compressed wood. However, flexural strength and modulus were less regarding other types of wood.